Foreign Practices in Land Cadaster Systems: An Experience for Ukraine - Kondratenko, Daria; Savchuk, Olena; Liubchych, Anna (European Journal of Sustainable Development, 2020)
The experience of European organizations managing land cadaster system is analyzed with examples of land relations development given for different spheres: legal, technical, and economic. The peculiarities in adoption and application of the 3D land cadasters by different countries of the world is viewed. It is stated that a cadaster of the future is to be a multi-purpose one in the 3D or 4D format. The need in modernizing current land legislation to improve the procedures of collecting, preserving, restoring, and utilizing land resources in Ukraine pertaining to implementation of the principle of the State land cadaster keeping is accentuated on. Advantages of account-and-registration systems are analyzed; the legal nature of social relations arising in this sphere is clarified. Recommendations concerning establishing the 3D cadaster in Ukraine are offered. Key words: lands account, cadaster systems, land, land parcels, the 3D cadaster.